Limb injuries in combat trauma: A retrospective analysis of 166 cases at a tertiary care center in counter insurgency operational area - Sanjay Maurya; Vipin V Nair; Onkar Singh; S K Singh (Journal of Marine Medical Society, 2020)
Background: Limbs are most commonly involved in combat trauma. There is insufficient data on limb injuries sustained in the combat zone of Indian Armed Forces. This study aims to analyze limb injuries in 166 cases at a tertiary care center in counter insurgency operational area. Materials and Methods: All casualties with limb injuries who presented to the center from January 2014 to December 2019 were included in the study. Data were obtained from admission and discharge registers, central registry, and operation theater registers. Casualties who were killed in action were excluded from the study. The extremity involved, wounding agent, type of injury, length of hospital stay (LOHS), number of surgical interventions, and type of reconstruction undertaken were recorded. Results: Limb injuries accounted for 61% of all casualties, with a mean age of 30.45% ± 6.72 years. Nearly 67% of all injuries were caused by fragmentation device, 61% were of soft-tissue (ST) type, and 39% were of ST injuries with fractures (STFs). The LOHS and number of surgical interventions for STFs were statistically significantly higher (P < 0.001). There was a moderate correlation between the grades of injuries, LOHS, and number of surgeries. The most common reconstruction undertaken was split skin graft in 32% cases. Conclusion: This study for the first time evaluates limb injuries in combat-related trauma in Indian Armed Forces. It also analyzes the LOHS, and number of surgeries with the type of injuries and their correlation.